Antropologia medica come antropologia politica della salute - Pizza, Giovanni (AM. Rivista della Società Italiana di Antropologia Medica, 2020)
Jennie Gamli, Sahra Gibbon, Paola M. Sesia and Lina Berrio (eds.), Critical Medical Anthropology. Perspectives in and from Latin America, UCLPress, London, 2020, 286 pp. [DOI: https://doi.org/10. 14324/111.9781787355828 (Series: Perspectives from Medical Anthropology)]